The Relationship Between Management Accounting Information and Managerial Decision Making in Small Companies in the New Medan Subdistrict - Ginting, Berupilihen Br; Martin, Martin; Mahyudin, Mahyudin (Jurnal Akuntansi Hukum dan Edukasi, 2025)
This study aims to analyze the role of Management Accounting System (SAM) in supporting strategic decision making in Small and Medium Enterprises (SMEs) in Medan Baru District through a literature review approach. In facing increasingly complex business challenges, relevant and timely information is a key factor in decision making. SAM as part of an organization's internal information system has an important role in providing quantitative and qualitative data that supports managerial processes, including in formulating effective business strategies. This research uses a literature study method by reviewing relevant accredited national journals published in the last five years. The study results show that proper SAM implementation can improve operational efficiency, support budgeting, cost analysis, and comprehensive business performance evaluation. In addition, the integration of SAM with information technology, as well as the utilization of non-financial information such as customer satisfaction and productivity, also enrich the strategic decision-making process. However, the study also found several barriers to SAM implementation in the SME sector, such as low accounting literacy, limited resources, and lack of technology adoption. Therefore, continuous education and assistance are needed so that SMEs are able to utilize SAM to the fullest in improving competitiveness and business sustainability.